Robotic plant watering system based on the arduino microcontroller - Nass, O. V.; Yessengali, K. K. (Zhangir khan West Kazakhstan agrarian-technical university, 2017)
The article summarizes the experience of creating and programming a robotic device on the Arduino Uno platform. The research was carried out on the basis of the Scientific Research Institute of the «Zhangir Khan West Kazakhstan Agrarian Technical University». The main task of creating this device was to exclude the forgetfulness or inattention of users and prevent damage to the plant due to lack or excessive watering. The created device includes a soil moisture sensor that acts as a sensing element in an automated system. Watering depends of type plant and environmental parameters and is carried out only when it is necessary the plant, herewith the exact (minimum) amount of water is used. The resulting robotic system is aimed at reducing user time for watering plants, as well as minimizing water losses.
Наука и образования № 4 (49) 2017 г
Keywords: Arduino Microcontroller; Soil moisture sensor; water pump motor; Plant watering; Robotic watering system